Ancient Greek Parody “Convivium Atticum” and Mosaics in the Style “Asarotos oikos” (“unswept room/floor”) - Ermolaeva, Elena L. (Actual Problems of Theory and History of Art, 2015)
The author of the paper studies a piece of ancient Greek parody “Convivium Atticum” (I, 1–122) written by Matro of Pitane (4th–3rd centuries BC). She discusses the enigmatic Homeric cento passage of this parody describing a feast: “As for the sea-urchins with their long, spiny hair, I cast them away, / and they produced an uproar as they rolled about among the slaves’ feet / in an open space, where the sea’s waves always wash, / and they pulled many spines out by the roots from their head” (I, 18–21). The question is why the narrator throws the sea-urchins, delicious food, down onto the floor. I argue with the different interpretations of this passage, and turn to the newest data, to mosaics in the style of “Asarotos oikos” (“unswept floor”) that had not been yet taken into consideration. Pliny in his “Natural History” described the most famous work in that genre — the one by Sosos in Pergamon. Popular in the Hellenistic time, mosaics depict the remnants of banquets, among which are empty shells of the sea-urchins.
Keywords: Ancient Greek epic gastronomic parody; Hellenistic mosaics; style of “Asarotos oikos” (“unswept floor”); feast; cento poetry